Analysis of E-commerce Growth in the Industrial Age 4.0 in Indonesia - Yasep Azzery (International Journal of Engineering Continuity, 2022)
Trading transactions that were originally conventional began to change to the digital economy along with developments technology and the industrial era which is starting to enter the 4.0 era. Scheme E-commerce transactions between buyers and sellers occur through a digital platform, which is assisted by courier services. Revolution Industry 4.0 where every industrial activity will be integrated by IoT, Big data and cloud. With a SWOT analysis consisting of the four components namely Strength, Weakness, Opportunity, Threats will outline the points and analyse the growth of the world of E-commerce in the future industrial era 4.0 expected to open up new business opportunities for the younger generation in particular.